Maxillary anterior cortical bone thickness: An imperative parameter for implant solidity - 3-dimensional cone beam CT study - Shalu Rai; Deepankar Misra; Mansi Khatri; Tarun Vyas; Poulomi Bhakta; Priyank Mallick (Wolters Kluwer Medknow Publications, 2020)
Background: This study aims to evaluate alveolar height, buccal, and palatal cortical bone thickness using cone beam computed tomography (CBCT) useful for radiological pre-assessment for various surgical procedures of maxillary anterior region. Materials and Methods: Maxillary central and lateral incisors and canines were bilaterally evaluated in 200 selected patients. Images were obtained with New Tom CBCT and traced with New Net Technologies software. Alveolar height and cortical bone thickness at 3 mm, 6 mm, and 9 mm above the cemetoenamel junction were measured and statistically analyzed. Results: Significant differences in alveolar height were found genderwise and agewise and were found to be highest in age groups of 51-60 years and lowest in 11-20 years. Buccal thickness at 3 mm, 6 mm, 9 mm was highest in right central incisor, right central incisor and left central incisor and lowest in right canine, left canine and left canine, respectively. Palatal thickness at 3 mm, 6 mm, 9 mm was highest in right central incisor, left central incisor and left central incisor and lowest in left canine, left canine, and left canine, respectively. Bucco-palatal thickness at 3 mm, 6 mm, 9 mm was highest in left canine, right central incisor and left central incisor and lowest in right lateral incisor, respectively. Agewise and genderwise significant differences in buccal and palatal bone were found at different levels. Conclusion: Buccal bone is thinner than palatal bone; thus, require careful radiological appraisal in orthodontic tooth movement and any surgical procedure in this region.